PERILAKU HIDUP BERSIH DAN SEHAT DITINJAU DARI TINGKAT LITERASI KESEHATAN STUDI DI SDN 02 PENANGGAL - CANDIPURO KABUPATEN LUMAJANG - Anis Sukowati; Nurul Mawaddah; Ika Suhartanti; Eka Diah Kartiningrum (MEDICA MAJAPAHIT, 2025)
Health literacy on clean and healthy living behavior in elementary schools is very important to be instilled from an early age to improve the degree of health. This study aims to determine the relationship between health literacy level and clean and healthy living behavior at SDN 02 Penanggal, Candipuro District, Lumajang Regency". This study used a Non-Experimental research design with a Cross Sectional approach. The population in this study was 28 students of grades V-VI SDN 02 Penanggal, Candipuro District, Lumajang Regency. The sampling technique uses total sampling. This research instrument used a health literacy questionnaire and a PHBS questionnaire. Data analysis using the Spearman Rho test. The results showed that most of the health literacy of SDN 02 Penanggal students, Candipuro District, Lumajang Regency was adequate for 21 respondents and clean and healthy living behavior in the high category of 22 respondents from 28 samples. The results of the data analysis showed that the correlation efficiency between the level of health literacy and clean and healthy living behavior was positive, which was 0.905 which means that the relationship between the two variables is unidirectional, the more adequate the level of health literacy, the higher the clean and healthy living behavior. The results of the Spearman Rho test show that the p value is 0.000 < p 0.05 so that H1 is accepted.The conclusion of the results of this study is that the level of health literacy has a relationship with clean and healthy living behavior at SDN 02 Penanggal, Candipuro District, Lumajang Regency.